Antioxidant and antibacterial activity of extracts, fractions and isolated substances from the flowers of Acacia podalyriifolia A. Cunn. ex G. Don - Cláudia Alexandra de Andrade; João Luiz de Souza Carvalho; Miriam Machado Cunico; Ana Luísa Lacava Lordello; Carmen Etsuko Kataoka Higaskino; Siumara Costa da Cruz Almeida; Josiane de Fátima Gaspari Dias; Vitor Alberto Kerber; Marilis Dallarmi Miguel; Obdúlio Gomes Miguel (Universidade de São Paulo, 2010)
The extracts and fractions from the flowers of A. podalyriifolia were analyzed previously for antibacterial activity using diffusion in disk, Antioxidant properties were evaluated by determining radical scavenging power (DPPH test) and total phenol content was measured (Folin method). The present study describes the in vitro antibacterial (determining minimum inhibitory concentration) and antioxidant activities (by thiobarbituric acid reactive species - TBARS method) for the ethanol extract, dichloromethane and ethyl acetate fractions and two flavanones (naringenin and 5-β-D-glycosyl-naringenin) isolated from the flowers of Acacia podalyriifolia A. Cunn. ex G. Don. The flavanones naringenin and 5-β-D-glycosyl-naringenin had not previously been obtained from this species. The most effective antibacterial activity was observed in the ethyl acetate fraction (MIC=0.25 mg mL-1 against Staphylococcus aureus ATCC 6538, MIC = 0.125 mg mL-1 against Staphylococcus epidermidis ATCC 12229, MIC=0.5 mg mL-1 against Streptococcus pyogenes ATCC 19615, Klebsiella pneumoniae ATCC 13883 and Proteus mirabilis ATCC 43071). The evaluated samples showed antioxidant activity on the TBARS test, especially for ethanol extract (1000 ppm), which was the most active (29.43% ± 0.65) followed by ethyl acetate fraction (1000 ppm, 24.84% ± 1,28), both demonstrating higher activity than that presented by ascorbic acid (1000 ppm, 21.73% ± 1.77), although lower than the BHT (1000 ppm 35.15% ± 3.42), both reference compounds. Naringenin and 5-β-D-glycosyl-naringenin demonstrated antioxidant action, but only naringenin inhibited the growth of gram-positive and gram-negative bacteria. Os extratos e frações de Acacia podalyriifolia foram analisados previamente para a atividade antibacteriana através da difusão em disco e as propriedades antioxidantes foram verificadas pela determinação da capacidade removedora do radical livre DPPH e pela mensuração do conteúdo de fenólicos totais (Método de Folin). O presente estudo descreve as atividades antibacteriana (determinação da concentração inibitória mínima) e antioxidante (espécies reativas do ácido tiobarbitúrico - teste TBARS) para o extrato etanólico e as frações diclorometano e acetato de etila e para duas flavanonas (naringenina e 5-β-D-glicosil-naringenina) isoladas das flores de Acacia podalyriifolia A. Cunn. ex G. Don. As flavanonas naringenina e 5-β-D-glicosil-naringenina ainda não haviam sido obtidas desta espécie. A atividade antibacteriana mais efetiva foi observada com a fração acetato de etila (CIM=0,25 mg/mL contra Staphylococcus aureus ATCC 6538; CIM=0,125 mg/mL, contra Staphylococcus epidermidis ATCC 12229; CIM=0,5 mg/mL contra Streptococcus pyogenes ATCC 19615, Klebsiella pneumoniae ATCC 13883 e Proteus mirabilis ATCC 43071). As amostras avaliadas demonstraram atividade pelo teste TBARS, especialmente o extrato etanólico (1000 ppm), que foi o mais ativo (29,43% ± 0.65), seguido pela fração acetato de etila (1000 ppm, 24,84% ± 1,28), ambos demonstrando atividade mais elevada que a apresentada pelo ácido ascórbico (1000 ppm, 21,73% ± 1,77), ainda que menor que a do BHT (1000 ppm, 35,15% ± 3,42), ambas substâncias de referência. Naringenina e 5-β-D-glicosil-naringenina demonstraram ação antioxidante, porém somente a naringenina inibiu o crescimento de bactérias gram-positivas e gram-negativas.